2000
DOI: 10.3133/ofr00336
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Folsom Lake response to historical and potential future climate scenarios

Abstract: An integrated forecast-decision system for Folsom Lake (California) is developed and used to assess the sensitivity of reservoir performance to various forecast-management schemes under historical and future climate scenarios. The assessments are based on various combinations of inflow forecasting models, decision rules, and climate scenarios and demonstrate that (1) reliable inflow forecasts and adaptive decision systems can substantially benefit reservoir performance and (2) dynamic operational procedures re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(33 citation statements)
references
References 9 publications
(10 reference statements)
1
32
0
Order By: Relevance
“…Nevertheless, this was seen in a few cases and, more often, a trade-off between reliability and sharpness was highlighted. This is in accordance with other studies (Hamlet and Lettenmaier, 1999;Yao and Georgakakos, 2001). …”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Nevertheless, this was seen in a few cases and, more often, a trade-off between reliability and sharpness was highlighted. This is in accordance with other studies (Hamlet and Lettenmaier, 1999;Yao and Georgakakos, 2001). …”
Section: Resultssupporting
confidence: 82%
“…] that low skill in reproducing regional precipitation is an index of the utility of GCM information for systems acting as low-pass filters, such as the hydrological and reservoir systems are". They found that this conditioning was particularly efficient to forecast the 30-day low-inflow volumes to the Folsom lake, and that the GCM-conditioned ensemble outperformed ESP (Yao and Georgakakos, 2001).…”
Section: Selecting Ensembles For Long-range Forecastingmentioning
confidence: 99%
See 1 more Smart Citation
“…Reliable forecasts on seasonal streamflow have tremendous economic and environmental worth, ranging from more effective water supply planning [1][2][3], improved flood and drought management [4][5][6][7], and increased hydropower generation [8][9][10], among others. The worth is particularly evident in semi-arid areas including the State of California, which largely relies on snow melt from the Sierra Nevada to supply water in meeting the State's increasing demand induced from its growing economy and population.…”
Section: Introductionmentioning
confidence: 99%
“…Such model evaluation is simpler for regions such as California that have consistently long dry seasons that reduce interannual dependency. Finally, the evaluation of the reliability of the longer-term ensemble flow forecasts is paramount to their effective use for water resources management ͑e.g., Georgakakos et al 1998;Yao and Georgakakos 2001͒.…”
Section: Operational Forecast Procedures and Modelsmentioning
confidence: 99%